Implementasi Kebijakan Hak Restitusi terhadap Anak Korban Kekerasan Seksual Sebagai Wujud Keadilan Restoratif - Arbain Nurdin (Amicus Curiae: Journal of Law and Justice Dialogue, 2025)
The escalation of sexual violence against children in Indonesia, particularly acts categorized as rape, has reached an alarming stage. Statistical data indicate that incidents of rape occur approximately once every four hours. In responding to crimes of sexual violence against children, two primary approaches are generally adopted. The first approach emphasizes the imposition of severe criminal sanctions on perpetrators. The second approach focuses on the recovery of child victims through restitution mechanisms. Developments in criminal law demonstrate that legal reform has the potential to influence social change by ensuring compensation or restitution for child victims of criminal acts. This research aims to examine the implementation of restitution rights for victims of child sexual violence as regulated under Government Regulation of the Republic of Indonesia Number 43 of 2017, as well as to analyze the application of restorative justice through the fulfillment of restitution for child victims of crime. This study employs a normative legal research method based on library research. The findings reveal that restitution, as regulated under PP RI No. 43 of 2017, constitutes a legal right of child victims of crime. Furthermore, the willingness and active participation of victims, perpetrators, and the community in addressing criminal conduct represent fundamental elements in the realization of restorative justice in cases involving child victims.